2016
DOI: 10.16943/ptinsa/2016/v82i1/48390
|View full text |Cite
|
Sign up to set email alerts
|

Population Gennetical, Behavioural and Evolutionary Studies in the Drosophila Bipectinata Species Complex

Abstract: Comparison of population dynamics with regard to chromosomal arrangements, protein and nucleotide polymorphism among closely related species can provide invaluable glimpses into the intricacies of speciation. In addition, recently diverged closely related species may also exhibit behavioural differences especially sexual behaviour which can be compared across the species and eventually may aid in understanding the process of speciation. To get the finer details of the so called 'speciation genes', evolutionary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Given such small nucleotide divergence, morphological differences (among the males of three species) are far from being just barely evident, they are in fact very prominent). In addition to this, there are behavioural differences and strong reproductive isolation among these species (see review by Singh and Banerjee 2016). Therefore, more than divergence at the level of single nucleotides, rearrangement of gross chromosomal blocks must have played a greater role and have influenced regulation of gene expression in a big way causing speciation.…”
Section: Discussionmentioning
confidence: 99%
“…Given such small nucleotide divergence, morphological differences (among the males of three species) are far from being just barely evident, they are in fact very prominent). In addition to this, there are behavioural differences and strong reproductive isolation among these species (see review by Singh and Banerjee 2016). Therefore, more than divergence at the level of single nucleotides, rearrangement of gross chromosomal blocks must have played a greater role and have influenced regulation of gene expression in a big way causing speciation.…”
Section: Discussionmentioning
confidence: 99%
“…However, these three species are distantly related to D. pseudoananassae. Based on asymmetrical mating pattern, it has been suggested that D.parabipectinata is derived from D. bipectinata (Singh & Banerjee, 2016). Thus as far as speciation is concerned, both isolating mechanisms are important: sexual isolation (premating) and hybrid sterility (post mating) in this complex.…”
Section: Drosophila Bipectinata Species Complexmentioning
confidence: 99%
“…The present work has been done on Drosophila malerkotliana, a species thatbelongs to D. bipectinataspecies complex (Banerjee & Singh, 2017;Singh et al 2015;Singh & Banerjee, 2016;Singh & Singh, 2001). Among the Drosophila species that occur most commonly in the Indian subcontinent, this species is highly prevalent.…”
Section: Introductionmentioning
confidence: 99%